Puss in boots:hello friend (Hello friend India, 1993)
A clever cat, Puss in Boots, uses his wits to elevate his poor master's status. He tricks a king and a ogre to gain wealth and favor. Through cunning and charm, Puss helps his master win the hand of a princess, proving that intelligence can triumph over adversity.